Is arthroplaSty bEtter than interNal fixation for undiSplaced femoral nEck fracture? A national pragmatic RCT: the SENSE trial. Issue 10 (10th October 2020) - Viberg, Bjarke; Kold, Søren; Brink, Ole; Larsen, Morten Schultz; Hare, Kristoffer Borbjerg; Palm, Henrik
Abstract : Introduction: Undisplaced femoral neck fractures (FNFs) are usually treated by internal fixation (IF) but two randomised controlled trials (RCTs) have demonstrated advantages of treatment with arthroplasty. The complication rate was lowered but there were no clinically improved patient-reported outcome measures (PROM), which could be due to underpowering or choice of selected PROM as the studies do appear to report a better functional outcome. We will conduct an RCT comparing IF with arthroplasties in patients aged over 65 years with an undisplaced FNF. Methods and analysis: All hospitals in Denmark treating patients with hip fracture can provide patients for this study; therefore, the study can be considered a national RCT. Patients over 65 years old with an undisplaced FNF will be screened for eligibility and patients will only be excluded if they are unable to understand the study information (due to dementia or language), if they have a posterior tilt >20°, a pathological fracture or they cannot walk. Participants will be electronically randomised (in alternating blocks of 4 or 6) into either IF or arthroplasty. Postoperative care will follow the department standards. Primary and secondary outcomes and measuring points have been established in collaboration with patients with hip fracture by focus group interviews. The primary outcome measure is the New Mobility Score assessed after 1 year. Secondary outcomes are the Oxford Hip Score, EuroQol 5 domain (EQ-5D-5L), degree of posterior tilt, pain Verbal Rating Scale, reoperation and mortality. Ethics and dissemination: The study is approved by the Danish Data Protection Agency (19/7429) and the scientific ethics committee (S-20180036). All participants will sign an informed consent before entering the trial. Because this is a national trial, all relevant healthcare professionals in Denmark will automatically receive the trial results that will be published in international peer-reviewed journals. Trial registration number: ClinicalTrials.gov Registry (NCT04075461 ).